Identification of the Active Compound Content of Red Union (Allium Cepa L) Originating from Aceh - Evi Dewiyani; Muhammad Ridhwan; Husna Husna; Masyudi Masyudi (Universitas Serambi Mekkah, 2022)
The incidence of Dengue Hemorrhagic Fever (DHF) is still high and is a public health problem in Indonesia. One of the efforts to eradicate it is to control the vector, namely the Aedesaegypti mosquito. Eradicating adult mosquitoes through fogging using an insecticide with the active ingredient malathion and sprinkling Abate powder for a long period of time continuously can actually result in non-target animal deaths, loss or death of natural enemies, environmental damage in the form of ecosystem imbalance and Aides population resistance. Utilization of natural materials as an alternative effort that is environmentally friendly and not harmful to other organisms needs to be done. Previous research found that shallot skin (Allium cepa L) contains flavonoid compounds which can be larvicidal, alkaloids, polyphenols, sesquiterpenoids, monoterpenoids, steroids, triterpenoids, acetogenins and quinones. In this study researchers used shallots. This type of research was experimental, which was conducted at the MIPA laboratory at Serambi Mekkah University, the shallots were taken from onion farmers in South Aceh District. The results showed that leeks were extracted using ethanol solvent through FTIR analysis with visible wave absorption indicating the presence of functional groups OH, CH alkanes, C=C cycloalkanes, and CO indicating the presence of flavonoid compounds. GCMS analysis revealed that the shallots from Aceh contain Hexadecanoic acid methyl ester, Octadecadienoic acid and Octadecatrienoic acid. Keywords: Red union (Allium cepa L.); larvicides; Aedesaegypti.